2000
DOI: 10.1136/heart.83.3.290
|View full text |Cite
|
Sign up to set email alerts
|

Patients with uncomplicated coronary artery disease have reduced heart rate variability mainly affecting vagal tone

Abstract: Aim-To investigate whether uncomplicated chronic coronary artery disease causes changes in heart rate variability and if so, whether the heart rate variability pattern is diVerent from that described in patients with acute myocardial infarction. Methods-Heart rate variability was studied in 65 patients with angina who had no previous myocardial infarcts, no other diseases, and were on no drug that could influence the sinus node. Results were compared with 33 age matched healthy subjects. The diagnosis of coron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
33
0
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 17 publications
4
33
0
3
Order By: Relevance
“…The activity of the autonomic nervous system is reflected in the heart rate variability (HRV) [6][7][8]. Several authors have demonstrated depressed long-term HRV in patients with underlying cardiovascular disease [9][10][11] and HRV has proved to be highly predictive for cardiovascular morbidity and mortality in these patients [12][13][14]. Recently, short-term HRV analysis (5 min) has been shown to be a reliable tool to predict hypotension after spinal anaesthesia [15,16].…”
mentioning
confidence: 99%
“…The activity of the autonomic nervous system is reflected in the heart rate variability (HRV) [6][7][8]. Several authors have demonstrated depressed long-term HRV in patients with underlying cardiovascular disease [9][10][11] and HRV has proved to be highly predictive for cardiovascular morbidity and mortality in these patients [12][13][14]. Recently, short-term HRV analysis (5 min) has been shown to be a reliable tool to predict hypotension after spinal anaesthesia [15,16].…”
mentioning
confidence: 99%
“…[11] B Wennerblom et al analyzed the HRV in patients with uncomplicated CAD and found a reduction of HRV in the higher spectrum of frequencies. [5] Kunz et al demonstrated that patients with CAD had a lower complexity of HRV, greater sympathetic modulation, and lower parasympathetic modulation. [12] A change in the balance between the sympathetic and the parasympathetic nervous system is associated with increased risk of arrhythmias such as ventricular fibrillation, resulting in sudden death of patients.…”
Section: Discussionmentioning
confidence: 99%
“…[4] It is reported that a major part of the government exchequer has to be spent on managing subjects with CAD and serious complications arising out of the disease. [5] The list of risk factors in the causation of the disease is long but still incomplete. One of the newly emerging risk factor is the alteration in the autonomic balance of the heart.…”
Section: Introductionmentioning
confidence: 99%
“…T IME-DOMAIN analysis of heart rate (RR) time series improves the diagnosis and prognosis of some cardiac and neural disorders [1], [2]. Indexes such as the standard deviation of normal-to-normal RR time series quantify heart rate variability (HRV) regardless of its rate of variation.…”
Section: Introductionmentioning
confidence: 99%